First albinism report for the wild guinea pig Cavia tschudii (Mammalia: Rodentia) - Ramirez, Dámaso W. (2019)
In wild mammals, atypical coloration patterns such as albinism occur at a low frequency and are poorly reported in the literature. Therefore, discovery of cases of coloration anomalies are important to better understand this phenomenon. Here, we describe the first reported case of albinism in Cavia tschudii “Wild Guinea Pig” from the central coast of Peru. This discovery also represents the first record of albinism for the genus Cavia in the Neotropics.